Efeito de dietas ricas em óleo de peixe ou soja sobre mediadores inflamatórios e dano oxidativo do DNA na colite experimental - Munhoz, Karina Vieira de Barros [UNIFESP] (2009)
Background: Ulcerative colitis (UC) is characterized by recurrent episodes of colonic inflammation with an imbalance in the synthesis and release of cytokines. Chronic colonic inflammation has been associated with DNA damage and colorectal cancer. Dietary polyunsaturated fatty acids (PUFA), can modulate immune function, inflammation and carcinogenesis. Therefore, we investigated whether PUFA could influence colonic injury, plasma corticosterone and tissue myeloperoxidase activity (MPO), DNA damage and cytokines in colitic rats. Methods: Male weaning Wistar rats were fed for 47 days with an AIN-93 diet with control (C), fish (F) or a mixture of fish and soybean oil (SF). UC was induced from day 36 until day 42 by 3% DSS in drinking water. On day 48, the rats were anesthetized and, blood samples were collected for corticosterone determination. The distal colon was excised for histological analysis and to quantify the cytokine (IL- 4, IL-10 and INF-g), MPO and DNA damage. The disease activity index (DAI) was recorded daily during colitis induction. Results: DAI, MPO, histological analyses showed decreases (p<0.05) only in the SF group compared with the C group. IL-10 was increased and DNA damage was reduced in the groups F and SF, and an inverse correlation between these variables (r=0.77) was found. There were no differences in corticosterone, IFN-g and IL-4 levels. Conclusions: Soybean and fish oil mixture may be effective in improving colonic injury and DNA damage, and it could be an important complementary therapy in UC to reduce the use of anti-inflammatory drugs and prevent colorectal cancer. Running head: PUFA and colonic inflammation